2002
DOI: 10.1001/archinte.162.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyaluronate Sodium on Pain and Physical Functioning in Osteoarthritis of the Knee

Abstract: For resting pain relief, hyaluronate sodium seems to be as effective as NSAIDs. Further, for pain with physical activity and functional performance, hyaluronate sodium may be superior to placebo alone or NSAIDs alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(50 citation statements)
references
References 24 publications
2
42
0
6
Order By: Relevance
“…The procedure is associated with few local adverse events and decreases the need for concomitant analgesia/ therapeutic modalities. Activity related pain seems to respond better to HA injection which is similar to previous studies [36]. The need for long-term study cannot be over emphasized.…”
Section: Resultssupporting
confidence: 88%
“…The procedure is associated with few local adverse events and decreases the need for concomitant analgesia/ therapeutic modalities. Activity related pain seems to respond better to HA injection which is similar to previous studies [36]. The need for long-term study cannot be over emphasized.…”
Section: Resultssupporting
confidence: 88%
“…Only 4 trials reported concealment of allocation and blinding of the outcome observer, and presented data from an intention-to-treat analysis. 12,22,31,33 Seven trials reported allocation concealment. 12,22,29,[31][32][33][34] Eight trials reported an intention-to-treat analysis, but only 6 of these presented data that could be extracted from the intention-to-treat analysis.…”
Section: Trial Qualitymentioning
confidence: 99%
“…55 Viscosupplementation with hyaluronan is as effective as NSAIDs for improving resting pain and may provide superior relief from pain with physical activity (recommendation strength A). 56 Intraarticular injections are usually completed as a series of 3 to 5 injections with benefits lasting 12 weeks or longer. 56 Two hyaluronan compounds (high molecular weight and low molecular weight) with no appreciable difference in efficacy are commercially available (recommendation strength A).…”
Section: Office Interventionsmentioning
confidence: 99%
“…56 Intraarticular injections are usually completed as a series of 3 to 5 injections with benefits lasting 12 weeks or longer. 56 Two hyaluronan compounds (high molecular weight and low molecular weight) with no appreciable difference in efficacy are commercially available (recommendation strength A). 57 Acupuncture has also been shown to have benefits in relieving chronic symptoms in limited studies (recommendation strength B).…”
Section: Office Interventionsmentioning
confidence: 99%